2012
DOI: 10.1177/1477153512458671
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of Evalglare software, daylight glare probability and high dynamic range imaging for daylight glare analysis

Abstract: The latest glare metric, called daylight glare probability (DGP), has been developed specifically for daylight glare issues inside a building. Unlike other glare indices, DGP considers vertical illuminance values at the human eye when evaluating different levels of discomfort glare. One of the options to calculate DGP is to use a high dynamic range imaging (HDRI) technique and Evalglare glare analysis software. This paper briefly shows USC Watt Hall 3rd floor interior glare study results and explains the incon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 5 publications
0
23
0
1
Order By: Relevance
“…Glare is a multi-facetted and complex phenomenon. While a few automated tools have been developed to assist in quantitatively analyzing the relationship between glare and visibility in architectural spaces (e.g., [28, 29]), little is currently known about how to extend these tools to account for significant levels of low vision. Contrast sensitivity decreases at low light levels [30] and is affected by both spatial and temporal adaptation [12, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Glare is a multi-facetted and complex phenomenon. While a few automated tools have been developed to assist in quantitatively analyzing the relationship between glare and visibility in architectural spaces (e.g., [28, 29]), little is currently known about how to extend these tools to account for significant levels of low vision. Contrast sensitivity decreases at low light levels [30] and is affected by both spatial and temporal adaptation [12, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Recently developed Daylight Glare Probability (DGP) metric is formed basing on the experimental results of a research and is calculated with Equation 3 (Jakubiec, Reinhart, 2012). In several studies using DGP method, better correlation with human subject's response is found compared to DGI (Jakubiec, Reinhart, 2012;Suk, Schiler, 2013). In this metric, glare probabilities higher than 30% are found to cause perceptible glare for the occupants.…”
Section: Assessment Of Façade Designs In Terms Of Control Of Glarementioning
confidence: 99%
“…This new method was implemented in the lighting calculation engine Radiance [18], through the purposely-developed tool Evalglare [19]. The calculation of DGP requires a High Dynamic Range (HDR) image (a photography or an image generated through a simulation) and a long computation time (especially for an annual glare analysis) to process luminances/illuminances in the scene with respect to one or more positions and directions of observations [20]. Moreover, a study by Pierson et al [21] highlighted how a superficial understanding of the input data for Evalglare may lead to an inappropriate detection of glare sources, which in turn may determine an inaccurate estimation of glare indices.…”
Section: Introductionmentioning
confidence: 99%